ANALISIS KEPUASAN PASIEN BERDASARKAN ASPEK PELAYANAN DAN KOMUNIKASI INTERPERSONAL (Studi Pada Pasien RSUD Datu Beru Takengon Kab. Aceh Tengah) - Rizkan Abqa; Win Konadi; Musrizal Musrizal (IndOmera, 2023)
The research aims to analyze patient satisfaction at the Datu Beru Takengon Regional General Hospital (RSUD) to obtain empirical input regarding the influence of service quality factors and interpersonal communication carried out by medical and non-medical employees in caring for patients and patient families. The research was based on a survey of 50 samples of patients who had previously used hospital services, with an associative type and using a path analysis model. The results of the research show that (a) there is a causal relationship (associative) between service quality and interpersonal communication between medical and non-medical personnel at Datu Beru Takengon Regional Hospital with a strong category (0.845), (b) Service quality factors have a causal relationship (associative) has an impact on cause and effect (associative) relationships. positive towards patient satisfaction, with a direct and indirect contribution of 46.55%. And the interpersonal communication aspect of RSUD officers was 30.58%. (C). Simultaneously, the quality of service and interpersonal communication at RSUD Datu Beru Takengon contributed to patient satisfaction, namely 77.10%.